Evolution of the genomes of two nematodes in the genus Caenorhabditis - Coghlan, Avril (Trinity College (Dublin, Ireland). Department of Genetics, 2004)
The soil-dwelling nematode Caenorhabditis elegans has been intensively studied as a model organism for the last 40 years. It was the first animal for which we had a complete description of development, anatomy, a neural wiring diagram, and, in 1998, a genome sequence. In 2001 the genome of Caenorhabditis briggsae was sequenced. They are the first pair of animals from the same genus to have their genomes sequenced. The two worms are very similar morphologically and follow similar developmental programs, but are surprisingly dissimilar genetically. I compared their genomes to identify syntenic regions that have been conserved since they diverged 80-110 million years ago. I found the rate of chromosomal rearrangement to be exceptionally high in these nematodes compared to in most eukaryotes. After the C. briggsae genome was sequenced in 2001, an important step was the prediction of protein coding genes in the raw sequence. I describe how my collaborators and I predicted genes in the C. briggsae genome; com pared C. briggsae genes to those of C. elegans-, and used similarity to C. briggsae to improve gene predictions in C. elegans. Intron-exon structure has evolved rapidly: I estimated there have been 0.005 intron gains or losses per gene per million years since the two species diverged. To elucidate the mechanism of intron gain, I pinpointed intron-exon differences that were due to intron gain rather than loss. My results narrow down the probable mechanism of intron gain to just two of the five hypothesised mechanisms.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin